Pemanfaatan Metode Tes Cepat Molekuler (XPERT MTB/RIF) Di Kabupaten Sorong Tahun 2014-2018 - Kristina Kristina; Dina Bisara Lolong; Dian Perwita Sari (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2020)
Tuberculosis (TBC) is one of the health problems in the world, including in Indonesia. According to the World Health Organisation, the adult population is more exposed to TBC. An early TBC case finding is required to prevent disease transmission. The delay in diagnosis of TBC cases and treatment irregularities increase the chances of transmission in the community. The molecular rapid-test (MRT) examination can more accurately detect cases of confirmed TB culture than the microscopic one. Sorong District Hospital has conducted the molecular rapid-test to diagnose TBC since 2014.. This study aims to describe the utilization of MRT in Sorong Regency from 2014-2018. This research used a cross-sectional design. The population were TBC suspects who were examined by MRT at the District Hospital. The samples were all TBC suspects referred to the Sorong District Hospital for MRT examinations from 2014 to July 2018. The secondary data collected from the patient identity, the origin of referral, the type of specimen examined, the purpose of examination, the patient treatment status, and MRT examination results. Most of the MRT examinations were male (54.5%), aged 15-54 years (71.3%), the origin of referrals from internal health facilities (38.7%) and the health centre (37.8%). The MRT examination of most TBC patients with re-treatment cases was 88-90% in 2014-2016 and 53-66% in 2017-2018. Every year, drug-resistant TBC (RO) tests ranged (47-87%). Total MRT examination results obtained 25.7% rifampin sensitive, and 5% rifampin resistant. Conclusion: Most of the MRT examinations were male, aged 15-54 years. The origin of the referral was from the internal health facility/hospital. The purpose of examination was mostly from the drug-resistant TB tests. The results of MRT examination diagnosed 25.7% of new TBC cases and 5% of drug-resistant TBC from the total of 1,528 examinations. Abstrak Penyakit tuberculosis (TBC) merupakan masalah kesehatan di dunia, termasuk di Indonesia. Menurut WHO (World Health Organization) populasi orang dewasa lebih banyak terpapar TBC. Penemuan kasus TBC sedini penting dalam upaya pencegahan penularan penyakit. Keterlambatan diagnosis kasus TBC dan ketidak teraturan pengobatan memperbesar peluang transmisi di masyarakat. Pemeriksaan tes cepat molekuler (TCM) dapat mendeteksi lebih akurat kasus konfirmasi kultur TBC dibanding dengan pemeriksaan mikroskopik. RSUD Kabupaten Sorong telah menerapkan penggunaan metode diagnosa TBC dengan tes cepat molekuler sejak 2014 hingga saat ini. Tujuan penulisan artikel untuk mengetahui gambaran pemanfaatan TCM di Kabupaten Sorong dari Tahun 2014-2018. Disain penelitian potong lintang. Populasi adalah suspek TBC yang diperiksa TCM di RSUD Kabupaten sedangkan sampel adalah semua suspek TBC yang dirujuk ke RSUD Kab Sorong untuk pemeriksaan TCM periode 2014-Juli 2018. Data sekunder yang dikumpulkan: identitas pasien, asal rujukan, jenis specimen yang diperiksa, tujuan pemeriksaan, status pengobatan pasien, dan hasil pemeriksaan TCM. Pemeriksaan TCM sebagian besarlaki-laki (54,5%), umur 15-54 tahun (71,3%), asal rujukan dari internal faskes (38,7%) dan Puskesmas (37,8%). Pemeriksaan TCM sebagian besar pasien TBC kasus pengobatan ulang yaitu 88-90% tahun 2014-2016 dan 53-66% tahun 2017-2018. Setiap tahun pemeriksaan TBC resisten obat (RO) berkisar (47-87%). Dari seluruh total pemeriksaan TCM diperoleh hasil 25,7% rifampisin sensitive, dan 5% rifampisin resisten. Kesimpulan: Pemeriksaan TCM sebagian besar laki-laki, umur 15-54 tahun, dan asal rujukan dari internal fasyankes/rumah sakit. Tujuan pemeriksaan sebagian besar memeriksa TBC resisten obat. Hasil pemeriksaan TCM mendiagnosa 25,7% kasus TBC baru dan 5% TBC resisten obat dari 1.528 pemeriksaan.